Characterization of small thermal structures in RFX-mod electron temperature profiles. (13th April 2016) - Fassina, A; Gobbin, M; Spagnolo, S; Franz, P; Terranova, D
Abstract: In the RFX-mod reverse field pinch (RFP) experiment, electron temperature profiles often feature structures and fluctuations at fine scale. The present work aims at characterizing their occurrence and their localization, in particular by linking them to underlying tearing modes magnetic islands. The confinement characteristics are discussed, identifying analogies with respect to high scale T e structures. Finally, high frequency magnetic activity (i.e. microtearing instabilities) is confirmed to be closely correlated to the presence and proximity of temperature gradients.